2015
DOI: 10.5966/sctm.2015-0111
|View full text |Cite
|
Sign up to set email alerts
|

Sphere-Derived Multipotent Progenitor Cells Obtained From Human Oral Mucosa Are Enriched in Neural Crest Cells

Abstract: The sphere culture technique is a convenient method for isolating stem cells. However, the isolation and characterization of human oral mucosa stromal cells (OMSCs) using the sphere culture system are not fully understood. The present study describes the isolation of neural crest progenitor cells from oral mucosa using this system. Human OMSCs form spheres that exhibit self-renewal capabilities and multipotency, and are enriched with neural crest-derived cells. These oral mucosa sphere-forming cells can genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 52 publications
4
68
0
Order By: Relevance
“…Consistent with our results, Davies et al suggested that NC‐derived progenitors in oral mucosa possess a multipotent capacity 10 . Also, a recent study showed that human oral mucosa‐derived cells were capable of differentiating into NC lineages in vitro and generated ectopic bone tissues in vivo 36 . Since abundant GFP‐positive NCDCs were seen in buccal mucosa, we consider that this type of tissue may be beneficial to harvesting NCDCs for use in regenerative medicine strategies.…”
Section: Distribution and Clinical Potential Of Ncdcs In Oral And Densupporting
confidence: 91%
“…Consistent with our results, Davies et al suggested that NC‐derived progenitors in oral mucosa possess a multipotent capacity 10 . Also, a recent study showed that human oral mucosa‐derived cells were capable of differentiating into NC lineages in vitro and generated ectopic bone tissues in vivo 36 . Since abundant GFP‐positive NCDCs were seen in buccal mucosa, we consider that this type of tissue may be beneficial to harvesting NCDCs for use in regenerative medicine strategies.…”
Section: Distribution and Clinical Potential Of Ncdcs In Oral And Densupporting
confidence: 91%
“…In human, the confirmation of the presence of neural crest cells in adult tissues is less obvious and mainly based on their expression profile, associated with their differentiating capacity and their ability to follow migration pathways when injected in chicken embryos. In those conditions, adult human NCSC have been identified in skin [2832], hair follicle [30,31], in dental pulp [3336], periodontal ligament [37,38], in cornea [39], inferior turbinate [40], olfactory or oral mucosa [41,42] and in adipose tissue [43]. …”
Section: Discussionmentioning
confidence: 99%
“…One of the major challenges facing the field of stem cell-based tissue engineering, including 3D bio-printing of complex tissues and organs, particularly the neural tissues, is the lack of a readily accessible source of stem cells. Previous studies have demonstrated that numerous adult tissues, including most of the oral and craniofacial tissues, originate from ectoderm-derived migratory neural crest cells during development 25 , 26 , while specific subpopulations of adult progenitor cells 27 , particularly those from oral and craniofacial tissues 16 , 28 30 , confer neural crest stem-like cells properties. Most recently, we have shown that GMSCs of neural crest-origin could be easily and readily converted into neural progenitor-like cells and exhibited enhanced capability of differentiating into neuronal and Schwann cells both in vitro and in vivo 17 .…”
Section: Discussionmentioning
confidence: 99%